2017
DOI: 10.1111/cid.12537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of volumetric dimensional changes in posterior extraction sites with and without ARP using a novel imaging device

Abstract: The dimensional loss in postextraction sockets grafted with anorganic bovine bone substitute and covered by a resorbable collagen barrier was lower than that of the naturally healing sites. However, ridge preservation was able to maintain almost 80% of the pristine bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…No significant differences between the groups were found for any of the parameters analyzed ( p > .05). The results of the present study are in line with previously published data, demonstrating changes of the soft tissue contour along with changes of the hard tissues following tooth extraction (Araujo & Lindhe, ; Araújo, Silva, Mendonça, & Lindhe, ; Barone et al, ; Clozza et al, ; Jung et al, ; Sbordone et al, ; Schneider et al, ). However, methodological differences hamper a direct comparison of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences between the groups were found for any of the parameters analyzed ( p > .05). The results of the present study are in line with previously published data, demonstrating changes of the soft tissue contour along with changes of the hard tissues following tooth extraction (Araujo & Lindhe, ; Araújo, Silva, Mendonça, & Lindhe, ; Barone et al, ; Clozza et al, ; Jung et al, ; Sbordone et al, ; Schneider et al, ). However, methodological differences hamper a direct comparison of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using a different primary outcome (expressed in mm 3 ) and two bone substitutes with porcine origin, Barone et al () found a mean loss of 244 mm 3 (pre‐hydrated collagenated cortico‐cancellous porcine bone group) and 349 mm 3 (cortical porcine bone group) after only 3 months. Another RCT with a negative control group and a DBBM test group (Sbordone et al, ) presented similar findings when compared to a previous study (Barone et al, ), always demonstrating an overall reduction from the original volume (expressed in mm 3 ), with a reduction of 400 mm 3 at control group and 210 mm 3 at DBBM group after 5 months. A recent RCT evaluating soft tissue changes in posterior sites after 6 months (Tomasi et al, ) found interesting results, where the DBBM‐C showed a soft tissue remodeling of 21.3%, a similar amount in the negative control group (20%).…”
Section: Discussionmentioning
confidence: 99%
“…A negative value representing a bone loss. Implant survival: an implant was considered to have survived as already described in previous. papers and in addition when functionally loaded and lost at the removing time. Implant crown survival: an implant crown was considered to have survived unless fractured in the restorative material or upon fracture or loosening of the abutment/retaining screw or not in place because of implant loss or implant fracture.…”
Section: Methodsmentioning
confidence: 99%
“…When ridge preservation therapies were performed at extraction sites, they resulted in a statistically significant reduction of postextraction dimensional changes . A 1.83 mm decrease in resorption of the alveolar ridge width and 1.47 mm decrease in vertical height loss was found in one study …”
Section: Introductionmentioning
confidence: 94%
“…Ridge preservation procedures have been developed with the aim of reducing the dimensional changes of alveolar bone after tooth extraction; this, in turn, will facilitate subsequent prosthetic treatment using dental implants by allowing a more optimal implant placement in accordance with the occlusal scheme . Both preclinical and clinical studies have investigated the changes which occur after tooth extraction when the site is left to heal on its own and when ridge preservation procedures have been performed …”
Section: Introductionmentioning
confidence: 99%